CHEMICAL DE-EMULSIFICATION OF SOME IRAQI WET CRUDE OILS (Journal of Engineering, 2002)
Production of Wet crude oil has been a growing field problem worldwide. Applications of the i:- .c methods and technologies to treat wet crude oil are needed to solve this problem and remove as much water as is economically possible. This paper deals with laboratory test to evaluate the relative efficiency of different emulsion breakets (de-emulsifiers) under different conditions.Five de-emulsifiers were used to treat wet crude oil from East Baghdad and Kirkuk oilfields. On the basis of a laboratory study, it is shown that using RP6000 (commercial) and NIPD de-emulsifiers achieved the best results; the latter was introduced in the present work. The de-emulsification rate is inlluenced i:o a great extent by the de-emulsifier concentration.Finally, it is shown that water *in-oil emulsions formed from kirkuk crude oil (low viscosity's and asphaltenes content) are less stable and more easily broken than those from the more viscous and S highly asphaltenes, East Baghdad crude oil.